Formulation of Arabica Coffee Farming Business Development Strategy in Enrekang District Using SWOT Analysis - Najib, Marhawati; Afrinda; Syam, Agus; Jufri, Muhammad; Nurhalim (Economics and Business Journal (ECBIS), 2025)
Enrekang Regency is one of the famous Arabica coffee-producing areas because it has a topography and climate that are suitable for the growth of coffee plants. Despite having suitable land for coffee cultivation, most coffee farmers still face several problems both internally and externally. Therefore, research is needed to determine the strategy for developing Arabica coffee farming businesses in Enrekang Regency by examining the analysis of internal and external factors. This research is a descriptive study using a qualitative approach. Respondents in this study were coffee farmers and traders, determined intentionally. Data collection used in the study included observation, interviews, and documentation. The data obtained were analyzed using SWOT analysis. Based on the results of the study, it shows that the strategy applied to coffee farming is in quadrant one, namely Aggressive (growth-oriented strategy), or is in a dynamic growth position, or is in a strength-opportunity strategy position (using strengths to take advantage of opportunities in decision making). This shows that there is an opportunity to develop Arabica coffee farming, in addition to having greater strengths compared to its weaknesses, it also has greater opportunities compared to its threats.